Influence of timing of glucose drink ingestion on selected responses of wheelchair athletes - Spendiff, O.; Campbell, I. G. (Adapted Physical Activity Quarterly, 2004)
Seven athletes with low lesion paraplegia ingested a 7.6% 648ml glucose drink using two schedules of ingestion (4 3 162 ml per 20 min & 2 3 324 ml per 60 min) in a crossover design. Participants exercised at 65% peak oxygen uptake for one hour, followed by a 20-minute performance test. The cardiorespiratory responses during the one-hour tests were similar between trials. Plasma glucose concentrations significantly increased after ingestion and remained stable during the 162 trial, but reduced over time during the 324 trial. Free fatty acid concentrations increased for both trials but increased significantly more during the 324 trial. The results of this study suggest that the ingestion of glucose during exercise is the best strategy for wheelchair athletes competing in endurance events.